Virginia Apgar: in the struggle for newborn's life - N. A. Makatsariya; R. N. Minazetdinova (IRBIS LLC, 2022)
The article highlights historic aspects of medical and research work for one of the prominent anesthesiologists ever - Virginia Apgar.